Vocabulary knowledge in the comprehension of academic texts in efl learners at the technical University of Cotopaxi - Berrones Cevallos, Dylan Vinicio (2022)
Vocabulary Knowledge is more than just word recognition, it plays a fundamental role in reading comprehension, as it helps students understand the meaning of written texts and improve their mastery of all English skills. Therefore, this study aims to analyze the size of the vocabulary and the readability of reading comprehension of academic texts in pre-service English teachers in the seventh term at the Technical University of Cotopaxi. The method used was quantitative. In addition, it has a non-experimental, descriptive, and cross-sectional design. The participants were 40 pre-service English teachers of the seventh-cycle, class "A" at the Technical University of Cotopaxi, of which 22 students worked as a representative sample of the entire population. The instruments to collect data used in the study were the McLean & Kramer's (2015) New Vocabulary Level test (NVLT) and a Reading Comprehension Test (RCT) constructed by the researchers which was adapted to the research settings and validated by experts in the linguistics field. The results show that the size of vocabulary knowledge of these students is low compared to the level they are expected to have according to the curriculum of the Pedagogy of National and Foreign Languages major at UTC. In addition, their low vocabulary size might negatively influence their reading comprehension of academic texts.